Measurment of Salicylic Acid in Poplar's Bark (P. deltoides and P. euramerican) by High Performance Liquid Chromatography (HPLC) - J Torkaman; Sh Seyam (Institue of Medicinal Plants, ACECR, 2010)
Background: The family salicaceae included salix and populus species. This family especially salix alba is very important in ancient medicinal. Recognition and investigation on other species in this family can help to development of herbal medical in country. Objective: This study was done to measuring of salicylic acid in Populus deltoides and Populus euramerican. Methods: After collection and drying of barks, extraction was done according to TAPPI standard (T204 om-88) by using acetone, ethanol and water solutions. Measuring of Salicylic acid was done by HPLC (High Performance Liquid Chromatography). Results: The extractive materials yield of populus deltoides and populus euramerican's bark were obtained 12.2 and 17.7% respectively base on dry weight of bark. HPLC analysis shows that there are 32 compounds in water extractive materials which amount of two compounds are more than others. According to retention time one of two compounds is Salicylic acid. The Salicylic acid values in populus deltoides and euramerican bark extractive materials are 14.7 and 19.5 ppm respectively. Conclusion: Generally, this research show that populus species contains Salicylic acid which is lower than Salix alba. The amount of Salicylic acid in populus euramerican is more than populus deltoids. Hydrophobic compounds in populus euramerican are twice than populus deltoides. There is no significant difference between hydrophilic compounds of two species.